¿Regulation or competition? The case of the Argentine Law of Audiovisual Communications Services and the Proportionality Principle as a delimiting criterion - Aguilar Valdez, Oscar Rafael (2016)
The purpose of this article is to highlight the importance of the Proportionality Principle as a valid legal criterion to determine when a given industry must be ex ante regulated by the Government through a specific sectorial regulatory framework or whether the application of the general antitrust and competition laws to such industry must be considered as a valid alternative. To this ends, this article analyzes the case of the Argentinean Law of Audiovisual Communications Services as it was treated by the Supreme Court of Argentina in the Grupo Clarín case.